2014
DOI: 10.1115/1.4028431
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Heat Transfer Measurements on the Stator Endwall of an Axial Turbine

Abstract: In order to continue increasing the efficiency of gas turbines, an important effort is made on the thermal management of the turbine stage. In particular, understanding and accurately estimating the thermal loads in a vane passage is of primary interest to engine designers looking to optimize the cooling requirements and ensure the integrity of the components. This paper focuses on the measurement of endwall heat transfer in a vane passage with a three-dimensional (3D) airfoil shape and cylindrical endwalls. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Heat transfer measurements in the facility were performed with an infrared based technique described by (Lazzi Gazzini et al, 2017b) and (Laveau et al, 2014). A Flir IR SC7300L camera was used to record the temperature of the rotor endwall through infrared transparent Zinc-Selenide (ZnSe) windows installed in the rotor casing ( Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Heat transfer measurements in the facility were performed with an infrared based technique described by (Lazzi Gazzini et al, 2017b) and (Laveau et al, 2014). A Flir IR SC7300L camera was used to record the temperature of the rotor endwall through infrared transparent Zinc-Selenide (ZnSe) windows installed in the rotor casing ( Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Friedrich et al [29] of the German Aerospace Center carried out detailed experiments on the EGG transonic planar cascade, indicating that the separation of the HV ps started from a 40% axial chord length and was attached to 80% of the axial chord length. Similarly, in the study of Benoit Laveau et al [30], an experimental analysis of the turbine guide vane was conducted, and it was concluded that the HV ps separated from 30% axial chord length and attached to 75% of the axial chord length. Compared with non-expansion blades, the separation and attachment point of horseshoe vortex pressure surface had an advance of 15%.…”
Section: Secondary Flow In S2mentioning
confidence: 97%
“…The stationary rows consist of 36 vanes and the rotor is composed of 54 blades. More details of the experimental facility are presented by Behr et al 15 Recently, Laveau et al 16 installed and demonstrated the use of a heat transfer measurement platform in the first stationary row of the turbine in the LISA facility. Measurements of heat transfer quantities, namely the heat transfer coefficient and the adiabatic wall temperature, were performed using a specially developed measurement platform, providing a quasi-isothermal boundary condition.…”
Section: Lisa Turbine Facilitymentioning
confidence: 99%
“…Inlet profiles for total pressure, total temperature and turbulence intensity were obtained from corresponding experiments. 16 The corresponding turbulence length scale profile was determined in a separate CFD study for the inlet region of the test facility. Table 2 provides a summary of the range of the investigated boundary conditions.…”
Section: Cfd Modelmentioning
confidence: 99%